Comparison of metal accumulation in mussels at different local and global scales - Blackmore, Graham; Wang, Wenxiong (2003)
Cadmium and zinc uptake from the dissolved phase, assimilation efficiency (AE) from the dietary phase, and body burden as well as clearance rate were measured in green mussels, Perna viridis, and blue mussels Mytilus edulis, M. galloprovincialis and Mytilus trossulus. Perna viridis was collected from four sites differentially enriched with trace metals in Hong Kong and blue mussels were collected from different climatic zones, i.e., subarctic and temperate, to allow comparisons with the more tropical green mussels. Despite similar shell length, the dry weight of mussels varied significantly between sites and species and this had a large effect on Cd and Zn accumulation, clearance rate, and metal body burden. All data were, therefore, weight adjusted to allow comparison without this confounding factor. Trace-metal body concentrations were significantly different between sites, and P. viridis collected from Tsing Yi, Hong Kong, had the highest levels of all measured metals when compared with other Hong Kong sites. There was, however, no relationship between the degree of metal enrichment and the Cd and Zn uptake (both from dissolved and particulate sources) and clearance rates. Furthermore, Cd and Zn uptake (dissolved and particulate) and clearance rate varied little between species or climatic zones of collection. Thus, over the range of body trace-metal concentrations measured and between mussel species over large geographical distances and climatic zones, the uptake rates, AEs, and clearance rates are similar when measured under the same laboratory conditions after body-size correction. When other factors such as salinity are also corrected, biomonitoring data from different areas and even utilizing different mussel species may be directly comparable. This study therefore provides important evidence in support of Mussel Watch Programs.